The Identity of Gods People and the Paradox of Hebrews - Filtvedt, Ole Jakob (Mohr Siebeck, 2015)
Die Identität des Gottesvolkes und das Paradox des Hebräerbriefs.
PublicationDate: 20150803
Keywords: Christian Origins -- Gerichtsberichterstattung -- Supersessionism -- Concepts of the Divine -- Covenant -- Exempla -- Neues Testament -- New Testament